Career motivation, internship experience, and soft skills on work interest in students with the mediating role of work readiness perceptions - Nasrul Arifin Pohan; Mat Amin; Suhardi Suhardi (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
The dynamics of the modern job market require college graduates to not only excel academically but also possess adequate professional preparedness. This study aims to analyze the influence of career motivation, internship experience, and soft skills on the work interest of students at the Faculty of Economics and Business (FEB) of Pertiba University, with perceived work readiness as a mediating variable and Grade Point Average (GPA) as a control variable. This study used a quantitative approach with an explanatory design. Data were collected through a structured questionnaire distributed to final-year students who had participated in the internship program. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. The results showed that internship experience and soft skills had a positive and significant effect on perceived work readiness, while career motivation had no significant effect. Perceived work readiness was shown to partially mediate the relationship between internship experience and soft skills on work interest. Meanwhile, GPA did not show a significant effect on work interest. These findings emphasize the importance of strengthening practical experience and developing interpersonal competencies in higher education.